Sex as an Independent Prognostic Factor in a Population-Based, Non-Small Cell Lung Cancer Cohort - Marshall W Pitz; Grace Musto; Srisala Navaratnam (Canadian Respiratory Journal)
BACKGROUND: Males with non-small cell lung cancer (NSCLC) tend to experience worse outcomes, as do those with nonadenocarcinoma histology; however, the independent effects of these factors remain unclear.